Espionage against Poland in the Documents and Analyses of the Polish Special Services (1944 - 1989) - as Illustrated by the Intelligence Activities of the USA - Rosicki, Remigiusz (WNPiDz UAM, 2016)
The text is treats of the espionage against Poland in the period 1944-1989. The above analysis has been supplemented with the quantitative data from the period 1944-1984 as regards those convicted for participating in, acting for, and passing on information to the foreign intelligence agencies. The espionage issues were presented on the example of the American intelligence activity, which was illustrated by the cases of persons who were convicted for espionage. While examining the research thesis, the author used the documents and analyses prepared by the Ministry of Internal Affairs, which were in its major part addressed to the Security Service and the Citizens’ Militia officers. The author made an attempt at the verification of the following research hypotheses: (1) to what extent did the character of the socio-political system influence the number of persons convicted for espionage against Poland in the period under examination (1944-1989)?, (2) what was the level of foreign intelligence services’ interest in Poland before the year 1990?, (3) is it possible to indicate the specificity of the U.S. intelligence activity against Poland?
The text analyses the intelligence activity against Poland in the period 1944-1989. The paper also contains a case study, i.e. an analysis of the American intelligence service activity held against Poland. While examining the research thesis, the author used the documents and analyses prepared by the Ministry of Internal Affairs. In order to best illustrate the point, the author presented a number of cases of persons who spied for the USA, which was possible thanks to the analysis of the training materials of the Ministry of Internal Affairs directed to the officers of the Security Service and the Citizens’ Militia. The text tackles the following issues: (1) to what extent did the character of the socio-political system influence the number of persons convicted for espionage against Poland in the period under examination?, (2) what was the level of interest of the foreign intelligence services in Poland before the year 1990?, (3) is it possible to indicate the specificity of the U.S. intelligence activity against Poland? 1) The analysis of data indicates that the period 1946-1956 witnessed a great number of convictions for espionage, which is often associated with the peculiar political situation in Poland of that time. Up to 1953, the countries of the Eastern bloc had reproduced the Stalin’s system, which only ceased due to the death of Stalin himself. Since then, the communist systems gradually transformed into the system of nomenklatura. Irrespective of these changes, Poland still witnessed a wave of repressions, which resulted from the threats continuously looming over the communist authorities – combating the anti-communist underground movement, fighting with the Ukrainian Insurgent Army, the Polish government-in-exile, possible revisionism of borders, social discontent related to the socio-political reforms. Hence, a great number of convictions for espionage at that time could be ascribed to purely political sentences. Moreover, equally significant was the fact that the then judicial practice was preoccupied assessing negatively any contacts and relations with foreigners. This excessive number of convictions could ensue from other criminal-law provisions, which applied with respect to the crimes against the State, including espionage. What is also important is the fact that in the Stalin’s period the judiciary personnel acquired their skills and qualifications through intensive courses in law with the predominant spirit of the theory of evidence and law by Andrey Vyshinsky. Additionally, by the decree of 1944 the Penal Code of the Polish Armed Forces was introduced; the code envisaged the increase in the number of offences classified as penalised with death penalty, whereas the high treason was subject to the military jurisdiction (the civilians were prosecuted in military courts till 1955; the espionage, however, still stood under the military jurisdiction). In 1946, there was introduced the Decree on particularly dangerous crimes in the period of the State’s recovery, which was later called a Small Penal Code. 2) The interest that foreign intelligence services expressed in relation to Poland was similar to the one they had in all countries of Eastern and Central Europe. In the case of Poland, it should be noted that foreign intelligence services recruited Polish citizens who had previously stayed abroad and after WWII returned to their home country. The services also gathered information from Poles staying in immigrant camps (e.g. in FRG). The activity of the American intelligence service on the territory of FRG and West Berlin played a key role. The documents of the Ministry of Internal Affairs pointed to the global range of this activity, e.g. through the recruitment of Polish sailors in the ports of the Netherlands, Japan, etc. In line with the development in the 1970s, espionage, which had so far concentrated on the defence and strategic sectors, became focused on science and technology of the People’s Republic of Poland. The acquisition of collaborators in academic circles was much easier, as PRL opened to academic exchange. Due to the system of visas, the process of candidate selection for intelligence services (e.g. the American) began in embassies. In the 1980s, the activity of the foreign intelligence services concentrated on the specific political situation in Poland, i.e. the growing significance of the “Solidarity” social movement. 3) The specificity of the American intelligence activity against Poland was related to the composition of the residency staff, which was the largest in comparison to other Western countries. The wide range of these activities can be proved by the quantitative data of convictions for espionage in the years 1944-1984 (however, one has to bear in mind the factors mentioned earlier in the text, which led to the misinterpretation of these data). Analysing the data and the documents prepared by the Ministry of Internal Affairs, one should treat them with caution, as, frequently, the Polish counter-intelligence service used to classify the ordinary diplomatic practice and any contacts with foreigners as espionage threats. It is clearly visible in the language of the training materials concerned with “secret service methods of the intelligence activity” as well as in the documents on operational activities of the Security Service in relation to foreigners. The level of interest the USA had in Poland was mirrored in the classification of diplomatic posts, according to which Warsaw occupied the second place (the so-called Group “B”) on the three-point scale. The CIA experienced spectacular defeats during their activity in Poland: supporting the Polish underground anti-communist organisation Freedom and Independence and the so-called Munich-Berg episode (both cases took place in the 1950s). The text focuses only on selected issues related to the espionage activities against Poland. Similarly, the analysis of the problem has been based on selected sources, which has limited the research scope - however, it was not the aim of the author to present the espionage activity against Poland in a comprehensive way. In order to assess the real threat posed by the espionage activity, one should analyse the case of persons convicted for espionage in the period 1944-1989, as the available quantitative data, mentioned in the text, cannot constitute an explicit benchmark for the scale of espionage activity. The inaccuracies in the interpretation of data and variables, which can affect the evaluation of this phenomenon, have been pointed out in the text.
Keywords: bezpieczeństwo informacji; information security; bezpieczeństwo narodowe; national security; szpiegostwo; espionage; szpiegostwo USA; U.S. espionage; działalność wywiadowcza; intelligence activities; kontrwywiad; counterespionage; polski kontrwywiad; Polish counterintelligence; służby specjalne; special services